1. Rewrite the second equation in terms of x to isolate x.
2. Multiply the coefficient of y in the first equation by -8 and set it equal to the constant term of the second equation.
3. Solve the equation from step 2 to find the value of y.
4. Substitute the value of y into the second equation to find the value of x.
5. Verify that the values of x and y satisfy the first equation.
6. Multiply the coefficient of y in the first equation by -2 and set it equal to the constant term of the second equation.
7. Solve the equation from step 6 to find the value of y.
8. Substitute the value of y into the second equation to find the value of x.
9. Verify that the values of x and y satisfy the second equation.
10. The solution to the system of equations is the point (x, y) where x = 3 and y = -4.
Put the steps in order that are used to solve the following systems of equations by substitution. −7x−2y=−13
x−2y = 11 don't give me steps in words just put the numbers in order give me 10 steps
x - 2y = 11 --> x = 2y + 11
-16y = 64
-16y - 77 = -13
x - 2(-4) = 11
x + 8 = 11
y = -4
x = 3
-14y - 77 -2y = -13
-7 (2y + 11) -2y = -13
(3, -4)
1 answer